Eficiencia de diferentes plantas biocidas en el control del Spodoptera frugiperda (J.E.Smith) en condiciones de Laboratorio - Panduro Gonzales, Alberto (2005)
The present work has as title “Efficiency of different plants biocidas in the control of the Spodoptera frugiperda under conditions of Laboratory'', likewise with the objective to Determine the effect of the barbasco, patiquina, Tree of the paradise, Ojé, Mammee, Anona, Tobacco, and he/she Hits he/she hits, in the control of the Spodoptera frugiperda, in its different stages of biological cycle; he/she was carried out the present work in the Laboratories of Entomology of the Ability of Agrarian Sciences of the National University of San kingfisher, County of San Martin.; with an annual maximum T" of 32 °C, precipitation averages yearly of 1 200 mm and a relative humidity of 70-80%. The used design was totally at random of Designs (DBCA), with 9 treatments with five observations. The treatments were T1 (ANONA), T2 (OJE), T3 (he/she HITS he/she HITS), T4 (PATIQUINA), T5 (TREE OF THE PARADISE) T6 (MAMMEE), l7 {TOBACCO), T8 {BARBASCO), T4 (WITNESS). The results demonstrated that the biggest lethal effects obtained the treatment 6(MAMEY) with 91, 60%s, continued by the treatment 2 (OJE) with 83, 80%.